2013
DOI: 10.1016/j.juro.2012.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Muscle Derived Cell Therapy for Stress Urinary Incontinence: A Prospective, Dose Ranging Study

Abstract: Injection of autologous muscle derived cells in a wide range of doses appears safe with no major treatment related adverse events reported. In addition, treatment with autologous muscle derived cells shows promise for relieving stress urinary incontinence symptoms and improving quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
98
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(99 citation statements)
references
References 18 publications
0
98
0
1
Order By: Relevance
“…However, the efficacy results differ widely, as the methodology used for studies was very different, as described below. All studies were phase II prospective observational studies, except for 2 randomized studies [1,2], in which patients were randomized to different doses of stem cells.…”
Section: Resultsmentioning
confidence: 99%
“…However, the efficacy results differ widely, as the methodology used for studies was very different, as described below. All studies were phase II prospective observational studies, except for 2 randomized studies [1,2], in which patients were randomized to different doses of stem cells.…”
Section: Resultsmentioning
confidence: 99%
“…A pooled mean was calculated from all three resulting in an estimated base case cure rate of 68%. Although there are other studies in the literature showing similar efficiency for IVM, they were not included here due to lack of definition the 'cured' patient population [34,35]. All patients not included in the group of 'cured' were added to the group 'not cured', despite having shown improvements.…”
Section: Probabilitiesmentioning
confidence: 99%
“…94 Their potentiality to restore function vias direct effects on the underlying mechanisms leading to incontinence or voiding dysfunction has been evaluated in preclinical animal models and clinical trials, especially for SUI. [95][96][97] Mesenchymal Stem Cells (MSCs), Muscle-Derived Stem Cells (MDSCs), Adipose-Derived Stem Cells (ADSCs) and Urine-Derived Stem Cells (USCs) are the sources of stem cells investigated for therapeutic benefit in urologic applications. 95,[97][98][99] Clinical trials reported improvement in SUI, through great reduction in pad weight, diaryreported leaks and even a complete achievement of continence in women, with no serious adverse events (pain, bruising at biopsy or injection sites).…”
Section: Research In Incontinencementioning
confidence: 99%
“…[95][96][97] Mesenchymal Stem Cells (MSCs), Muscle-Derived Stem Cells (MDSCs), Adipose-Derived Stem Cells (ADSCs) and Urine-Derived Stem Cells (USCs) are the sources of stem cells investigated for therapeutic benefit in urologic applications. 95,[97][98][99] Clinical trials reported improvement in SUI, through great reduction in pad weight, diaryreported leaks and even a complete achievement of continence in women, with no serious adverse events (pain, bruising at biopsy or injection sites). 95 To date, stem cells have shown promising results for the treatment of voiding dysfunction.…”
Section: Research In Incontinencementioning
confidence: 99%
See 1 more Smart Citation